Cell adhesion in trypanosoma. In vitro studies of the interaction of Trypanosoma vivax with immobilized organic dyes - Fish, W.R.; Nelson, R.T.; Hirumi, H. (Wiley, 1987)
Certain bloodstream forms of Trypanosoma vivax have been shown to attach to Amicon Matrex™ Gel Green A dye beads in a manner similar to the in vivo binding of T. vivax to the inner surface of the tsetse fly proboscis. We now report an in vitro assay for trypanosome‐bead attachment and show that only the 9,10‐anthraquinone portion of the dye molecule is involved in the binding of trypanosomes to beads and that bead‐bound dyes with similar structures also support binding to differing degrees. The binding is dependent upon the amount of dye on the beads and this, and other evidence, suggests that an array of dye molecules, rather than individual molecules, may be the actual recognition site. Various external effectors, including temperature, soluble protein‐dye complexes, and serum of mice with chronic T. vivax infections, reduce trypanosome binding, indicating that at least one immunogenic trypanosome macromolecule is involved. The trypanosome‐bead interaction mimics the in vivo binding to tsetse proboscis and warrants closer examination as a model of trypanosome cell adhesion in the tsetse fly.